2013
DOI: 10.1093/ejcts/ezs709
|View full text |Cite
|
Sign up to set email alerts
|

The neoaortic root in children with transposition of the great arteries after an arterial switch operation†

Abstract: The neoaortic root in children after the arterial switch procedure develops differently from that in healthy children, but this is not evidently related to NeoAR development or associated heart defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Older age at time of ASO, presence of VSD, bicuspid pulmonic valve, previous PA banding, perioperative mild AR and higher neo-aortic root/ascending aorta ratio are risk factors for AR [98–100]. Neo-aortic root dilation is also a consequence of ASO [101, 102], especially if there is size discrepancy of the great arteries [103]. Fortunately, aortic root dilation has not been significantly progressive during the current duration of follow-up and has not been associated with acute aortic dissection or increased mortality [104].…”
Section: Life-long Follow-up Carementioning
confidence: 99%
“…Older age at time of ASO, presence of VSD, bicuspid pulmonic valve, previous PA banding, perioperative mild AR and higher neo-aortic root/ascending aorta ratio are risk factors for AR [98–100]. Neo-aortic root dilation is also a consequence of ASO [101, 102], especially if there is size discrepancy of the great arteries [103]. Fortunately, aortic root dilation has not been significantly progressive during the current duration of follow-up and has not been associated with acute aortic dissection or increased mortality [104].…”
Section: Life-long Follow-up Carementioning
confidence: 99%
“…Neoaortic regurgitation (NeoAR) is a common sequela affecting patients with the transposition of the great arteries (TGA) after an arterial switch operation (ASO) [1]. In most cases, NeoAR usually does not constitute a significant clinical problem, but some patients still require reoperation because the insufficiency tends to progress [2,3]. The reason for the common occurrence of neoaortic valve (NeoAoV) incompetence is multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…35 Hourihan et al also observed that the NAoR and PV annulus are already larger than in normal infants before the ASO. 8 An increased risk of NAoR dilation in TBA and TGA with VSD has previously been recognized, 13,16,18 highlighting the role of a significant VSD in the pathophysiology of NAoR dilatation. This is clinically relevant as the reintervention rate is higher in TGA patients with a VSD compared with those with an IVS.…”
Section: Neo-aortic Rootmentioning
confidence: 94%
“…The growth of the anastomoses of the great arteries and the competence of the native pulmonary valve (PV) and root, now functioning as the neo-aortic valve and root (NAoR), in the systemic circulation are important in the long term. [6][7][8] NAoR dilatation has been reported, [8][9][10][11][12][13][14][15][16][17] even in the first year post-ASO, [9][10][11] and the root continues to grow excessively, [15][16][17] at a rate >4 times normal. 9 The resulting aortic valve (AoV) regurgitation and aneurysm formation may require a reintervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation